On-demand mobile hypertension training for primary health care workers in Nigeria: a pilot study - Joseph Odu; Kufor Osi; Leander Nguyen; Allison Goldstein; Lawrence J. Appel; Kunihiro Matsushita; Dike Ojji; Ikechukwu A. Orji; Morenike Alex-Okoh; Deborah Odoh; Malau Mangai Toma; Chris Ononiwu Elemuwa; et al. (BMC, 2024)
Abstract Background Only one out of every ten Nigerian adults with hypertension has their blood pressure controlled. Health worker training is essential to improve hypertension diagnosis and treatment. In-person training has limitations that mobile, on-demand training might address. This pilot study evaluated a self-paced, case-based, mobile-optimized online training to diagnose and manage hypertension for Nigerian health workers. Methods Twelve hypertension training modules were developed, based on World Health Organization and Nigerian guidelines. After review by local academic and government partners, the course was piloted by Nigerian health workers at government-owned primary health centers. Primary care physician, nurse, and community health worker participants completed the course on their own smartphones. Before and after the course, hypertension knowledge was evaluated with multiple-choice questions. Learners provided feedback by responding to questions on a Likert scale. Results Out of 748 users who sampled the course, 574 enrolled, of whom 431 (75%) completed the course. The average pre-test score of completers was 65.4%, which increased to 78.2% on the post-test (P < 0.001, paired t-test). Health workers who were not part of existing hypertension control programs had lower pre-test scores and larger score gains. Most participants (96.1%) agreed that the training was applicable to their work, and nearly all (99.8%) agreed that they enjoyed the training. Conclusions An on-demand mobile digital hypertension training increases knowledge of hypertension management among Nigerian health workers. If offered at scale, such courses can be a tool to build health workforce capacity through initial and refresher training on current clinical guidelines in hypertension and other chronic diseases in Nigeria as well as other countries.